The Effect of Sales Growth, Capital Intensity, and Inventory Intensity on Tax Avoidance in Energy Sector Companies - Valentina Stefani Handoyo; Dwi Ermayanti Susilo (Proceeding International Conference on Digital Education and Social Science, 2025)
Tax constitutes one of the primary sources of government revenue and plays a vital role in financing national development. Nevertheless, in business practice, taxes are often perceived as a cost that reduces corporate profitability, thereby motivating firms to implement various tax planning strategies, including legally permissible tax avoidance through the exploitation of regulatory loopholes. The goals of this research are to examine the effects of sales growth, the cost-to-income ratio as a marker of capital intensity, and the tax avoidance. For tax avoidance using the Effective Tax Rate, focusing on companies in the Indonesian Stock Exchange between 2020 and 2024. This research uses a quantitative method, using secondary data from annual financial reports. The data were collected and analyzed by the researcher using many tests, such as classical assumption tests and multiple linear regression analysis. The results show that sales growth, capital utilization rate, and inventory levels is good and significant influence on tax avoidance. This suggests that these factors are associated with a higher tax burden and a lower likellihood of companies in tax avoidance. Collectively, one of the variables significantly influences tax avoidance. The study concludes that operational financial characteristics, particularly capital and inventory intensity, play a crucial role in shaping tax avoidance behavior within the energy sector.